FIELD SURVEY ON PAPAYA VIRAL DISEASES IN MAJOR PAPAYA GROWING DISTRICTS IN BANGLADESH - M. A. Kabir, F. Begum, A. N. Faruq J. Lee N.N. Tonu (International Journal of Research Science and Management, 2017)
To investigate the papaya viral diseases in Bangladesh, an extensive survey was conducted at 10 upazilas of 6 selected major papaya growing districts of Bangladesh to collect the information and present status of different virus diseases of papaya in field. With the assistance of DAE, 20 farmers from each upazila were selected for interview on the incidence and severity of viral diseases of papaya crop in the field at seedling, flowering and fruiting stage. Direct personal interview approach was adopted for collection of primary data. Collected data were compiled, analysis and summarized by SPSS Software. Results exhibit that 3 identified different viral symptoms from all over the working area at three distinct growth stage were selected for sample data collection. Ringspot, mosaic and leaf curl symptoms were found as common symptoms which cause severe damage to papaya. Experiment results revealed that from both at farmer’s level information and field survey inspection papaya ringspot symptoms were very destructive and cause severe losses of farmer’s papaya fields. After papaya ringspot, papaya mosaic and papaya leaf curl were ranked, it was determined that all of them were serious in investigated papaya growing areas. It was observed that ringspot in fruit, leaf curl in leaves and in seedlings, mosaic in fruit and leaves were most destructive.